Molecular characterization, expression analysis and RNAi knock-down of elongation factor 1α and 1γ from Nilaparvata lugens and its yeast-like symbiont. Issue 3 (4th November 2016) - Wang, W.X.; Zhu, T.H.; Li, K.L.; Chen, L.F.; Lai, F.X.; Fu, Q.
Abstract: In the present paper, four cDNAs encoding the alpha and gamma subunits of elongation factor 1 (EF-1) were cloned and sequenced from Nilaparvata lugens, named NlEF-1α, NlEF-1γ, and its yeast-like symbiont (YLS), named YsEF-1α and YsEF-1γ, respectively. Comparisons with sequences from other species indicated a greater conservation for EF-1α than for EF-1γ. NlEF-1α has two identical copies. The deduced amino acid sequence homology of NlEF-1 α and NlEF-1 γ is 96 and 64%, respectively, compared with Homalodisca vitripennis and Locusta migratoria . The deduced amino acid sequence homology of YsEF-1α and YsEF-1γ is 96 and 74%, respectively, compared with Metarhizium anisopliae and Ophiocordyceps sinensis . Reverse transcription-quantitative polymerase chain reaction (RT–qPCR) analysis revealed that the expression level of NlEF-1α and NlEF-1γ mRNA in hemolymph, ovary, fat body and salivary glands were higher than the midgut and leg tissue. YsEF-1α and YsEF-1γ was highly expressed in fat body. The expression level of NlEF-1α was higher than that of NlEF-1γ . Through RNA interference (RNAi) of the two genes, the mortality of nymph reached 92.2% at the 11th day after treatment and the ovarian development was severely hindered. The RT–qPCR analysis verified the correlation between mortality, sterility and the down-regulation of the target genes. The expression and synthesis of vitellogenin (Vg) protein in insects injected with NlEF-1α and NlEF-1γ double-stranded RNA (dsRNA) was significantly lower than control groups. Attempts to knockdown the YsEF-1 genes in the YLS was unsuccessful. However, the phenotype of N. lugens injected with YsEF-1α dsRNA was the same as that injected with NlEF-1α dsRNA, possibly due to the high similarity (up to 71.9%) in the nucleotide sequences between NlEF-1α and YsEF-1α. We demonstrated that partial silencing of NlEF-1α and NlEF-1γ genes caused lethal and sterility effect on N. lugen s. NlEF-1γ shares low identity with that of other insects and therefore it could be a potential target for RNAi-based pest management.